Intercellular Communication of Tumor Cells and Immune Cells after Exposure to Different Ionizing Radiation Qualities - Diegeler, Sebastian; Hellweg, Christine E. (Frontiers in Immunology, 2017)
Ionizing radiation can affect the immune system in many ways. Depending on the situation, the whole body or parts of the body can be acutely or chronically exposed to different radiation qualities. In tumor radiotherapy, a fractionated exposure of the tumor (and surrounding tissues) is applied to kill the tumor cells. Currently, mostly photons, but also electrons, neutrons, protons and heavier particles such as carbon ions are used in radiotherapy. Tumor elimination can be supported by an effective immune response. In recent years, much progress has been achieved in the understanding of basic interactions between the irradiated tumor and the immune system. Here, direct and indirect effects of radiation on immune cells have to be considered. Lymphocytes for example are known to be highly radiosensitive. One important factor in indirect interactions is the radiation-induced bystander effect which can be initiated in unexposed cells by expression of cytokines of the irradiated cells and by direct exchange of molecules via gap junctions. In this review, we summarize the current knowledge about the indirect effects observed after exposure to different radiation qualities. The different immune cell populations important for the tumor immune response are natural killer cells, dendritic cells and CD8+ cytotoxic T cells. In vitro and in vivo studies have revealed the modulation of their functions due to ionizing radiation exposure of tumor cells. After radiation exposure, cytokines are produced by exposed tumor and immune cells, and a modulated expression profile has also been observed in bystander immune cells. Release of damage-associated molecular patterns by irradiated tumor cells is another factor in immune activation. In conclusion, both immune-activating and -suppressing effects can occur. Enhancing or inhibiting these effects, respectively, could contribute to modified tumor cell killing after radiotherapy.